In-situ forming lithiophilic-lithiophobic gradient interphases for dendrite-free all-solid-state Li metal batteries. (August 2022) - Lin, Yanke; Wang, Tianshuai; Zhang, Leicheng; Peng, Xudong; Huang, Baoling; Wu, Maochun; Zhao, Tianshou
Abstract: Solid polymer electrolytes offer a promise for all-solid-state Li batteries due to their low cost and good processability. However, dendrites and the associated contact loss occurring at the undesirable Li/electrolyte interface during repeated plating and stripping remain a challenge. To address the issue, here, we propose to coat a thin layer containing Al/Li dual-salt onto the polyethylene oxide (PEO) electrolyte. When cycled with the Li metal anode, the salts are sequentially reduced, in-situ forming a lithiophilic Li-Al alloy-rich layer near the anode and a lithiophobic LiF-rich layer close to the electrolyte. The former improves the interfacial adhesion and regulates the Li nucleation, while the latter contributes to dendrite suppression due to its high interface energy against Li. As a result, the gradient interphase enables a Li/Li symmetrical cell to be stably cycled for over 1000 h without short circuits. Moreover, the full cell paired with the LiFePO4 cathode shows enhanced cyclability, retaining 89.1% capacity after 350 cycles at 0.5 C. A pouch cell using the dual-salt coated electrolyte demonstrates good performance and safety. This work provides a facile yet effective approach to construct functional interphase for achieving stable batteries using solid polymer electrolytes. Graphical Abstract: ga1 Highlights: A lithiophilic-lithiophobic interphase is created to stabilize Li anode interface. The interphase is in-situ formed via sequential reduction of Al/Li dual-salt. The interphase simultaneously addresses contact loss and suppresses dendrites. All-solid-state full battery with the interphase exhibits enhanced cyclability.